Vitamin D status of Sudanese Children with Sickle Cell Anemia (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: sickle cell anemia; 25 hydroxy vitamin d; calcium; alkaline phosphatase; bone fracture; osteomyelitis body mass index; hemoglobin